PRINSIP HARMONI BENTUK DALAM PERANCANGAN KARYA MAHASISWA DESAIN BUSANA AKS-AKK YOGYAKARTA - Danu Widiantoro; Yosephine Flori Setiarini (Jurnal Socia Akademika, 2021)
This research aims to analyze the implementation of the principle of harmony form of AKS-AKK Yogyakarta student fashion copyright work. The application of harmony is closely related to the design element, so indicators in this study include harmony in lines, harmony in a flat plane (shape), and harmony in a 3-dimensional field (form). This principle of harmony is essential as one of the elements in designing fashion. The object in this study is a fashion created by AKS AKK Yogyakarta students in 2021 with the theme of Gala Party fashion that uses traditional fabrics in the creation process. The population and the sample in this study amounted to 19 fashions. This research is qualitative descriptive research. The source of the data collection used was the results of questionnaires on 49 respondents. The results of the respondent's assessment revealed that the application of the principles of line harmony ( line ), field ( shape ), and shape (form) is good. The disadvantage lies in the details of cutting motif materials and the compatibility of decoration, color shapes, and the texture of fashion materials. Thus the results of this research can contain knowledge for the development of Education in the AKS-AKK Yogyakarta Fashion Design Study Program, especially for Fashion Copyright Design materials.